If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + 4) = 3(y + 1) Reorder the terms: 6(4 + y) = 3(y + 1) (4 * 6 + y * 6) = 3(y + 1) (24 + 6y) = 3(y + 1) Reorder the terms: 24 + 6y = 3(1 + y) 24 + 6y = (1 * 3 + y * 3) 24 + 6y = (3 + 3y) Solving 24 + 6y = 3 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 24 + 6y + -3y = 3 + 3y + -3y Combine like terms: 6y + -3y = 3y 24 + 3y = 3 + 3y + -3y Combine like terms: 3y + -3y = 0 24 + 3y = 3 + 0 24 + 3y = 3 Add '-24' to each side of the equation. 24 + -24 + 3y = 3 + -24 Combine like terms: 24 + -24 = 0 0 + 3y = 3 + -24 3y = 3 + -24 Combine like terms: 3 + -24 = -21 3y = -21 Divide each side by '3'. y = -7 Simplifying y = -7
| -10n+7=-9n-5 | | 2(4y-1)=6y | | 37x-21+19x=154 | | Bx+Gy=Kforx | | x+3=z-5 | | 217+x/(13.2-X)(32.8-X)=1.25 | | Ax+Fy=Kforx | | 1.25=217+x/(13.2-X)(32.8-X) | | -12n+6=-10n-2 | | 2(4a-7)+a=76 | | -37-(-43)=x/6 | | 2(4c-1)-6=3c+7 | | -7(t+1)=14 | | -7(t+1)=4 | | 1/2(18x+2)=3(3x-2)-3(x-7) | | 1/2(p+6)=7/2(3-p) | | 3x^2+(k-1)x-2=0 | | 27-19=4(x-6) | | -7x+1=9 | | 30+5y-12=17y-9-3y | | x+23+4x=-22-4x-27 | | -x(x-2)(x+2)(x+2)=0 | | b^12*b^10= | | -0.4x^2+2.2x+4.7=0 | | w^6*w^8= | | 5q^2-2bq-3=0 | | -4x+1=33 | | 2m/5+4=-10/9-3 | | P(2)-10P+22=0 | | 3(z-4)+6= | | -11/7=z-2/3 | | 2log(x-3)-log(x+1)=2 |